ANALYSIS OF MODERN DEVICES FOR WET CLEANING OF INDUSTRIAL DUST GASES - Azizjon Isomidinov (Western European Studies, 2023)
The article analyzes hydraulic, flow inertial and rotor dust cleaning devices that clean industrial dust gases in a wet way. Devices of this type are used to clean flue gases from industrial furnaces and technological waste gases. Scientific research and many patents have been studied on the designs of this type of devices. In the researches, the parameters studied during the process of cleaning dusty gas by the wet method were analyzed and the effect of surface contact elements on the device parameters was evaluated
Keywords: dust gas; wet method; hydraulics; rotor